University Gamblers: The Power of Persuasive Messaging in Television Advertising - Oduor, Nicholas (International Journal of Communication and Public Relation, 2025)
Purpose: To find out the influence of Television’s persuasive messages on sports betting among university students in Kenya. Methodology: The study employed a mixed method design. Both qualitative and qualitative data were used. Descriptive survey strategy was also used to gather and analyze data with the aim of understand the patterns, behaviors, and attitudes related to television’s message appeals and sports betting among university students in Kenya. The quantitative data was analysed using descriptive and inferential statistics. A regression model was employed to identify the relationship between the variables. Findings: The study established a strong relationship between message appeals and sports betting among university students in Kenya. The initial results, without moderating variables, yielded an R-squared value of 0.152. This indicates that 15.2% of sports betting could be explained by message appeals alone. However, when the moderating variable (media literacy) the R-squared value increased substantially to 0.431. This meant that, in the presence of the moderator, 43.0% of sports gambling was accounted for by message appeals. Furthermore, the p-values in both models were less than 0.05, ascertaining that the relationships were statistically significant. The study arrived at the conclusion that message appeal had a strong impact on betting patterns among university students in Kenya. Unique Contribution to Theory, Practice and Policy: The study was guided by Elaboration Likelihood Model (ELM). The core assumption for this model is that there are two routes in communication process namely central route and the peripheral route (Petty and Cacioppo, 1986). As of the central route the consumer of the relayed message actively processes it then makes judgement based on rational evaluation of the message content, such as the quality of arguments and supporting evidence. In peripheral route the receiver does not expend the cognitive energy to evaluate the arguments but is rather guided by peripheral cues (Akpan, Nda & Nketa, 2015). Advertisers will only meet their expectations when the consumers engage through the peripheral route.